Rotterdam dialogues : the critics, the curators, the artists - Gray, Zoë (Utrecht : Post editions, 2010)
- The critics. ##Is there still such a thing as editorial authority? / Tim Griffin & Edgar Schmitz ; Can criticism be a productive force for speculative thinking? / Sina Najafi, Sven Lütticken, Dieter Roelstraete ; Are there new audiences for art criticism? / Mark Rappolt ... [et al.] ; Workshop / led by Melissa Gronlund##- The curators. ##When is a biennial a success? / Bart De Baere ... [et al.] ; Has the rise of the independent curator affected art practice? / Kitty Scott & Seth Siegelaub ; Is the curator per definition a political animal? / Enrico Lunghi ... [et al.] ; Is curating narcissistic? / Ann Demeester & Jan Hoet ; Workshop / led by Raimundas Malašauskas##- The artists. ##The power of representation/The representation of power / Piero Golia, Sarah Morris, Pierre Bismuth ; Persona / Jimmy Robert ... [et al.] ; Total visibility / Willem de Rooj & Jeff Wall ; Workshop / led by Judy Radul##- What are you talking about now?
CCS Gent
boek